DISCRIMINATION AGAINST DOMESTIC WORKERS: STRUCTURALINEQUALITY AND THE URGENT NEED FOR PRIVATE LEGAL PROTECTIONTHROUGH INDONESIA’S DOMESTIC WORKER PROTECTION BILL - putri purbasari raharningtyas; Dellvin Sergio (Jurnal Paradigma Hukum Pembangunan, 2026)
2004 marked the first year for the Domestic Workers Protection Bill (RUU PPRT) to be passed as a law. 21 years later, Indonesia’s legislators still fail to see its urgency. Domestic Workers in Indonesia have a substantial role in sustaining a household, where the majority of them goes undocumented. Without a clear and formal agreement, Domestic Workers may face multitudes of discrimination and exploitation. With predominant Domestic Workers being women and/or underage, the vulnerability of this group becomes prominent, especially in highlighting the extremity of the dire need for legal protection. This paper sought to answer two questions, how does structural discrimination shape working conditions of domestic workers in Indonesia, and how can the Domestic Workers Protection Bill (RUU PPRT) address these systemic inequalities? Through a normative-juridical approach, this paper finds various structural victimization that may impede on the rights of these workers, ranging from economic structural victimization to social structural victimization. This paper also highlights current laws and regulations and how it failed to extensively protect Domestic Worker’s rights, this was also furthered by the ambiguity stance of Domestic Workers in Indonesia’s current legal frameworks. In conclusion, Indonesia still needs to address and acknowledge Domestic Workers as formal employees and ensure social and legal protection of their rights.